Role of Vascular Smooth Muscle Cell Phenotypic Switching and Calcification in Aortic Aneurysm Formation: Involvement of Vitamin K-Dependent Processes. Issue 7 (July 2019) - Petsophonsakul, Ploingarm; Furmanik, Malgorzata; Forsythe, Rachael; Dweck, Marc; Schurink, Geert Willem; Natour, Ehsan; Reutelingsperger, Chris; Jacobs, Michael; Mees, Barend; Schurgers, Leon
Abstract : Aortic aneurysm is a vascular disease whereby the ECM (extracellular matrix) of a blood vessel degenerates, leading to dilation and eventually vessel wall rupture. Recently, it was shown that calcification of the vessel wall is involved in both the initiation and progression of aneurysms. Changes in aortic wall structure that lead to aneurysm formation and vascular calcification are actively mediated by vascular smooth muscle cells. Vascular smooth muscle cells in a healthy vessel wall are termed contractile as they maintain vascular tone and remain quiescent. However, in pathological conditions they can dedifferentiate into a synthetic phenotype, whereby they secrete extracellular vesicles, proliferate, and migrate to repair injury. This process is called phenotypic switching and is often the first step in vascular pathology. Additionally, healthy vascular smooth muscle cells synthesize VKDPs (vitamin K-dependent proteins), which are involved in inhibition of vascular calcification. The metabolism of these proteins is known to be disrupted in vascular pathologies. In this review, we summarize the current literature on vascular smooth muscle cell phenotypic switching and vascular calcification in relation to aneurysm. Moreover, we address the role of vitamin K and VKDPs that are involved in vascular calcification and aneurysm.